2021
DOI: 10.1136/bmjopen-2021-050601
|View full text |Cite
|
Sign up to set email alerts
|

What do people with lung cancer and stroke expect from patient navigation? A qualitative study in Germany

Abstract: ObjectiveThis qualitative study investigated patients’ needs and wishes in relation to patient navigation.DesignA qualitative interview study was conducted. Participants were invited to take part in three in-depth interviews over a period of 6–12 months. Thematic analysis was used.SettingInterviewees were sought in the Berlin metropolitan area of Germany in academic university hospitals, in rehabilitation clinics and through self-help organisations.ParticipantsThe sample consisted of individuals diagnosed with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…We used a data-driven approach for the model development as group discussions based upon a series of underlying studies in which we assessed barriers to optimal care as well as resources of support from the perspectives of patients, care experts, and providers [ 7 , 40 42 ] (Fügemann et al, in preparation). In addition, we assessed patient’s expectations about what a navigation assistance is and what a navigator should do [ 43 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used a data-driven approach for the model development as group discussions based upon a series of underlying studies in which we assessed barriers to optimal care as well as resources of support from the perspectives of patients, care experts, and providers [ 7 , 40 42 ] (Fügemann et al, in preparation). In addition, we assessed patient’s expectations about what a navigation assistance is and what a navigator should do [ 43 ].…”
Section: Methodsmentioning
confidence: 99%
“…Further details of the interview study are described elsewhere [ 43 ]. This study was approved by Ethics committee of the Charité-Universitätsmedizin Berlin.…”
Section: Methodsmentioning
confidence: 99%
“…), the assessment of PN awareness and the most important tasks of PNs from the population’s perspective were discussed. Finally, following the theoretical framework proposed by Fillion and colleagues [ 19 ], described above, and taking into account the results from a qualitative interview study with twenty lung cancer and twenty stroke patients [ 1 ], three main tasks of PNs were defined. Respondents were asked to select which one they consider the most important task.…”
Section: Methodsmentioning
confidence: 99%
“…These barriers also exist in the German healthcare system. Above all, research has revealed that there is little coordination of patients’ continued care in Germany [ 1 ], difficulties due to complex care in multimorbid patients [ 2 ], fragmentation of the German healthcare system and separate organization of the inpatient and outpatient sector [ 3 , 4 ]. In addition to these system barriers, on the patients’ side, low health literacy [ 5 ]—especially of vulnerable groups, such as migrants or lower educated people [ 6 , 7 ]—or limited knowledge about further support offers [ 8 , 9 , 10 ] can restrict access to optimal healthcare.…”
Section: Introductionmentioning
confidence: 99%
“… 17 , 18 Patients' vulnerable health situation, in which they are confronted with numerous existential psychosocial issues in addition to the burden of physical symptoms, is made still more difficult by the necessary orientation in complex healthcare systems. 19 , 20 , 21 Reactions to this structural development include interprofessional networking, integrated care models, and navigation approaches. Some navigation issues are still unanswered, including where patient navigators or case managers should be located, what qualifications they require, which (care) tasks they should take on, when they should be deployed, and what their targets should be.…”
Section: Introductionmentioning
confidence: 99%